The multiway trees of hanoi - Jürgensen, Helmut; Wood, Derick (International journal of computer mathematics, 1983)
We consider the multiway generalisation of the binary Trees of Hanoi. We provide a recursive algorithm for its solution and prove its optimality. Finally we solve the simultaneous recurrence equations to give an exact formula for the minimal number of moves necessary.